Islamic Communication Strategy Of Nahdlatul Ulama On The Political Stage Through Regional Election Contestation In East Java - Hamim; Priyo Sadono, Teguh; Sigit Pramono, Bambang (Sahafa Journal of Islamic Communication, 2024)
Currently the existence of NU is under the auspices of the organization, but in political dynamics it is very calculated. This research discusses the strategic role of Nahdlatul Ulama (NU) in political dynamics through the contestation of Pilkada in East Java, focusing on the Islamic communication approach applied. As the largest Islamic organization in Indonesia, NU has a significant influence on the formation of public opinion, political communication patterns, and mass mobilization in the local political arena. This research explores howNU utilizes Islamic communication principles, such as da’wah bil hikmah, justice, and togetherness, to build an effective strategy in supporting certain candidates. Implicitly, NU has a higher position than parties in the political arena. In the context of political communication, the existence of NU cannot be separated from the role of kiai and santri, both in the front stage and the back stage. The research method used includes a qualitative approach with data analysis from in-depth interviews, literature studies, and participatory observation of the dynamics of Pilkada in East Java. The results showed that NU’s approach was not only oriented towards electoral politics but also reflected efforts to maintain social harmony and Islamic values in society. NU uses pesantren networks, religious leaders, and local cultural traditions as strong communication media to strengthen its influence. The research results of the concept of dramaturgy and role-playing carried out by the candidates, creating an atmosphere and conditions of interaction which then give its own meaning to the community. The emergence of this meaning is highly dependent on the social background of the community itself and forms a society that is able to adapt to various atmospheres, patterns of political life. Keywords: Islamic Communication; Dramaturgy; Nahdlatul Ulama